On the Use of Lightwave Power Transfer in Miniaturized Satellite Communication Systems - Kyriatzis, Nikolaos; Gkiaouris, Dimitrios; Tegos, Sotiris A.; Diamantoulakis, Panagiotis D.; Papanikolaou, Vasilis K.; Schober, Robert; Karagiannidis, George K. (2024 14th International Symposium on Communication Systems, Networks and Digital Signal Processing, CSNDSP 2024, 2024)
CubeSats have a significant impact on the satellite communications sector due to their ability to provide rapid, cost-effective, and adaptable improvements to existing satellite networks or to individual missions. The main challenge facing CubeSats is their energy sustainability. Towards this end, we are considering lightwave power transfer (LPT) technology from larger satellites in low earth orbit (LEO) as an alternative power source for CubeSats. We propose a strategy that includes a CubeSat satellite which harvests energy and communicates with a ground base station, utilizing the harvested energy. We formulate an optimization problem for the proposed strategy, aiming to maximize the total harvested energy. Simulation results validate the usefulness of our approach when considering practical assumptions about the satellite orbits.
CRIS-Team Scopus Importer:2024-09-20
Keywords: CubeSats; Lightwave Power Transfer (LPT); Satellite Network